Therapeutic Prospective of Synthesized Copper Nanoparticles using Hemidesmus indicus (R.Br.) on Lung Cancer cell Lines (A549) and its Antibacterial Effect against the Clinical Isolates - Mary, Deena Raj Kesari; Sukumar, Sujatha (Asian Journal of Biological and Life Sciences)
Background: Research into natural chemicals and nanotechnology has attracted considerable interest in the pursuit of novel treatment methods for infectious diseases and cancer. Aim: The current study intended to synthesize and analyse the potential of Copper Nanoparticles (CuNPs) with the aqueous extract derived from the Indian sarsaparilla leaf, Hemidesmus indicus (R. Br.). Materials and Methods: Apart from the current research was focused on characterizing the synthesized copper nanoparticles, utilized multiple analytical techniques, including UV, FTIR, SEM, SEM-EDAX and TEM. The synthesized nanoparticles that possessed the potential antimicrobial activity were performed against the nine organisms and compared with the crude plant extract. It was found that the nanoparticles exhibited a significant zone of inhibition than the crude plant extract. Moreover, examined the potential ability of the synthesized CuNPs using H. indicus (R.Br.) on MTT analysis performed in lung cancer cell lines (A549). Apart from the anticancer study further revealed that apoptotic induction of synthesized nanoparticles treated in vitro cell-based apoptosis progressed to its late stage, Cells emitted orange fluorescence, signifying condensation of chromatin or fragmentation, leading to uniform red/orange-stained nuclei of cells. Results: The significant nuclear changes seen in H. indicus CuNP-treated cells, such as condensation of chromatin and nuclear disintegration, further confirmed the trigger of cell death through apoptosis. Furthermore, to elucidate the molecular level alterations of significant candidate anti-apoptotic targets-AKT and mTOR, the gene expression analysis was performed using RT-PCR. Notably, the current research results proved the efficacy of the synthesized copper-based nanoparticles from H. indicus in lung cancer A549 cells by initiating the apoptotic progression compared to the crude plant extract. It was well proven by apoptotic staining assays and molecular level analysis. Conclusion: The present findings highlighted the promising visions and therapeutic potential of the combination of nanoparticles of copper coupled with the aqueous extract, hence H. indicus-based nanoparticles possessed empirically antimicrobial effect and anti-cancer properties.
Keywords: Copper nanoparticle; Crude extract; Gene expression; H. indicus; Lung cancer